Pre-service teachers’ knowledge of evidence-based classroom management practices in physical education: a test validation using item response theory - Berthold, Clemens; Jeisy, Eric; Baumgartner, Matthias (Frontiers in Education, 2025)
This study validated an assessment instrument measuring pre-service teachers’ professional knowledge of evidence-based classroom management practices in physical education. Drawing on a model of teacher competence that integrates knowledge, situation-specific skills, and performance, the study focused on the competence area of classroom management to ensure conceptual clarity and relevance. Data from 877 pre-service primary education teachers from four universities of teacher education were analyzed using item response theory to examine the instrument’s structure and psychometric properties. The findings indicate a unidimensional structure with satisfactory reliability and no evidence of bias related to demographic variables. Test scores showed a small positive correlation with situation-specific skills, reflecting construct validity, as these require additional distinct cognitive abilities while being conceptually related. However, the test’s items proved relatively easy, resulting in a mismatch between item difficulty and participant ability levels, and did not capture the expected differences across pre-service teachers at different stages of their training, potentially due to a ceiling effect. Together, these findings limit the test’s capacity to differentiate among higher-ability individuals, thereby constraining criterion validity. Despite these limitations, the results demonstrate the instrument’s capacity to measure knowledge about evidence-based practices in classroom management. Further refinement could enhance its discriminatory power at advanced knowledge levels. This assessment provides a foundation for exploring how knowledge shapes teachers’ perception, interpretation, decision-making, and performance, and could support efforts in teacher education to develop effective classroom management practices.